Iliopsoas abscess resulting from penetrating left colon cancer to the retroperitoneum. : Case report and literature review. - Liz, Alejandra; Cerchiari, Emilia; Gayo, Gonzalo; Lapiedra, Diego; Viola, Marcelo; Diamant, Marcelo (Cirugía del Uruguay, 2022)
Iliopsoas abscess secondary to perforation of colon cancer is an extremely rare and potentially life-threatening condition. Most tumors are mucinous adenocarcinomas. Its treatment its complex, as most patients need radical extended resections to achieve good oncological results, which are in turn, graved with higher morbidity and mortality. We present the case of a patient with a left colon mucinous adenocarcinoma penetrating to the iliopsoas muscle and the anterolateral abdominal wall that required a multivisceral resection including left colon, iliac muscle and crest and part of the anterolateral abdominal wall.